Late Radiation-Related Toxicities in Patients Treated for Early-Stage Cervical Carcinoma by Surgery and Adjuvant Radiotherapy: A Retrospective Imaging Study - Nadova, Katarina; Burghardtova, Miroslava; Fejfarova, Klara; Reginacova, Klaudia; Malikova, Hana (Pathology oncology research, 2021)
Surgical treatment is preferred therapy of early-stage cervical carcinoma. In the risk of cancer recurrence surgery is often followed by adjuvant radiotherapy. In our retrospective study we aimed at identifying late (≥6 months) and very late (≥5 years) radiation adverse effects on imaging scans as CT, PET/CT and MRI in patients who underwent successful treatment for cervical carcinoma by radical surgery combined with radiotherapy ± chemotherapy. We correlated imaging results with clinical manifestations. We selected young and middle-aged patients with long life expectancy, as late radiation-related toxicities may significantly affect their quality of life. Patients were selected from those who were primary diagnosed and treated between the years 1987-2011 and regularly visited our Oncology department in years 2011-2012. Following inclusion criteria were applied: age ≤55 years at diagnosis, clinical follow-up ≥5 years and at least one tomography scan ≥3 years after finished treatment. One hundred and three subjects were reviewed: 73 patients met all inclusion criteria, while 30 patients fulfilled the inclusion criteria except for available tomography scan ≥3 years after therapy. The mean imaging follow-up was 11.2 ± 7.6 years and the mean clinical follow-up was 15.0 ± 6.9 years. In 20 (27%) subjects 27 cases grade I radiation-related toxicities were found; 9 (33%) of those 27 cases were clinically silent. In 14 (19%) females only grade I toxicities were observed. Grade III-IV toxicities were found in 5 (6.8%) subjects. No grade V toxicities were observed. We concluded that severe late side effects caused by radiotherapy were exceedingly rare in females successfully treated for early-stage cervical carcinoma, only 1 bilateral osteonecrosis, 2 cases of ileus, and 2 potentially radiation-induced tumors were found. The majority of radiation-related comorbidities found on imaging scans were clinically silent.
Keywords: comorbidity; bone; radiační poranění; kombinovaná terapie; Humans; adjuvantní radioterapie; Radiotherapy, Adjuvant; následné studie; Female; dospělí; nádory děložního čípku; Radiation Injuries; cancer; lidé; complication; radiation-induced tumor; toxicity; počítačové zpracování obrazu; Image Processing, Computer-Assisted; Adult; ženské pohlaví; Positron Emission Tomography Computed Tomography; Retrospective Studies; prognóza; hysterektomie; Uterine Cervical Neoplasms; retrospektivní studie; Hysterectomy; lokální recidiva nádoru; Combined Modality Therapy; Neoplasm Recurrence, Local; PET/CT; Prognosis; Follow-Up Studies